A hybrid machining process combining micro-EDM and laser beam machining of nickel-titanium based shape memory alloy - Al-Ahmari, A.; Rasheed, M. Sarvar; Khan Mohammed, Muneer; Saleh, Tanveer (Taylor & Francis, 2016)
Micro-EDM is a slow process as compared to laser machining, on the contrary laser machining lacks good surface quality. To overcome the drawbacks of both these processes, this paper suggests a hybrid machining process which combines laser and micro-EDM processes for drilling micro-holes in advanced engineering materials such as Nickel-Titanium (Ni-Ti) based shape memory alloy. To achieve the objective of the suggested hybrid process, pilot holes are drilled with laser machine and rimmed out by micro-EDM drilling. The suggested process requires investigation of various combinations of micro-EDM drilling process conditions to obtain optimum machining parameters for the hybrid process. It has been found that the proposed hybrid machining process resulted in 50-65% reduction in machining time without affecting the quality of micro-holes as compared to the standard micro-EDM process.